CCAFS plays key role in the ClimateShot Global Action Agenda for Innovation in Agriculture which sets the stage for transforming agricultural innovation systems for people, nature and climate at COP26 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Since 2020, CCAFS has co-chaired (with the UK Foreign, Commonwealth & Development Office) and served as secretariat for the COP26 campaign on ‘Transforming Agricultural Innovation for People, Nature and Climate’. Launched at COP26, the ClimateShot Global Action Agenda for Innovation in Agriculture has mobilized around 200 allies behind four key objectives, with a view to close the ‘innovation gap’ in agriculture and food systems and meet the Paris Agreement goals. Progress against these objectives will be monitored and reported back.